The influence of gender roles on health seeking behaviour during pregnancy in Turkey - TOPUZOĞLU, AHMET; SAVE, DİLŞAD; AY, NADİYE PINAR; HIDIROĞLU, SEYHAN (TAYLOR & FRANCIS LTD, 2009)
Objectives To explore the impact of gender roles in relation to health seeking behaviour during pregnancy and childbirth. Methods The study was conducted in neighbourhoods with low antenatal care rates in three provinces of Turkey. The study population consisted of pregnant women who never got or discontinued antenatal care and their peers, families and community leaders. Sixteen focus group discussions and 125 in-depth interviews were conducted with a total of 239 participants. Results Pregnancy and childbirth are interwoven strongly with gender roles. Since the patriarchal system acknowledges women through the means of childbirth, women are expected to have many children. Hence women experience pregnancy as a burden and are not motivated to seek antenatal care. During pregnancy, only 'serious' conditions are considered as legitimate reasons for accessing care. However, the decision regarding whether a pregnant woman is seriously sick or not belongs to the responsibilities of elder women, which delays service use. Conclusions Providing information regarding the value of antenatal care also to elder women is essential in increasing the demand to the services. Incorporating gender perspectives into daily health practice and maintaining access to high quality reproductive care services are vital in reducing the gender based barriers to care.
Keywords: Gender; Pregnancy; Childbirth; Health seeking behaviour; Antenatal care; Service utilisation; ANTENATAL CARE; PRENATAL-CARE; MATERNAL HEALTH; WOMENS STATUS; SERVICES; BARRIERS; DIMENSIONS; FRAMEWORK; ATTITUDES